Why Do Migrants Return to Poor Countries? Evidence from Philippine Migrants' Responses to Exchange Rate Shocks - Yang, Dean (The Review of Economics and Statistics, 2006)
This paper distinguishes between target-earnings and life cycle motivations for return migration by examining how Philippine migrants' return decisions respond to major, unexpected exchange rate changes in their overseas locations (due to the Asian financial crisis). Overall, the evidence favors the life cycle explanation: more favorable exchange rate shocks lead to fewer migrant returns.A10% improvement in the exchange rate reduces the 12-month return rate by 1.4 percentage points. However, some migrants appear motivated by target-earnings considerations: in households with intermediate foreign earnings, favorable exchange rate shocks have the least effect on return migration, but lead to increases in household investment.